POLITICAL PARTICIPATION IN TRADITIONAL SOCIETY (CASE STUDY OF 2009 LEGISLATIVE ELECTION IN KANEKES VILLAGE) - Suryanjari, Enny; Suhanto, Suhanto (Journal of Social Political Sciences, 2022)
This study examines the political participation of the Baduy community in the form of voting in the 2009 Legislative Election. According to their belief, the Baduy are not assigned to participate in the General Election. To respect government regulations, they participated in elections 3 times with few participants (3%). In 2009 the Baduy community participated in the General Election with the number of participants reaching 21% of the Permanent Voters List. This study aims to determine the factors causing the increase in voter turnout. Qualitative research methods. Data collection techniques through in-depth interviews, observations, and literature searches. Research results: the increase in political participation in the form of voting in the 2009 General Election in Kanekes village was caused by persuasion by the Golkar party legislative candidate, H. Kasmin, to the customary government. Persuasion is done using traditional communication, namely face to face, the communicator is a person who is well known so that the communicant believes in the content of the message received. Finally, the traditional leaders agreed to hold the general election in Kanekes village. After the election was approved by traditional leaders, the Golkar party’s success team consisting of Baduy people conducted a campaign to the citizens by utilizing primordial ties, namely ethnic ties.